STUDI KELAYAKAN RELOKASI PENUMPANG TERMINAL MUSTOKOHARJO SEBAGAI SALAH SATU BENTUK APLIKASI MANAJEMEN PUBLIK KABUPATEN PATI - CAROLINE, Ibu (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
In the implementation of regional autonomy Regency / City in general will have three functions: allocation, distribution and stabilization. Implementation of local government functions in the areas of allocation, among others, are providing services and public facilities, which are embodied in the construction of terminals in the Village Mustakaharjo Pati regency. With the construction of this terminal will boost economic growth and support the development of Pati district surrounding the city, given enough Pati District strategic location adjacent to the Holy District, Jepara, Grobogan, Blora and Rembang. Location of this study is the Village Mustakaharjo Pati regency. The analysis used analysis tool net present value (NPV), payback period analysis, Analysis of Return on Investment (ROI), Analysis of the results of return (internal rate of return) / IRR and the analysis of government-private cooperation. The conclusions obtained are potential high traffic density in this region will provide income opportunities (Cash In Flow) of Rp 176 611 583 .. The investment cost of development in the region of Rp 30,765,745,000. With a limit of 25-year investment period, then obtained: DF 10%, payback period is 19 years, 1 month, DF 12%, is not feasible (above 25 years), DF 14%, it is not feasible (above 25 years)